Institutional culture towards addressing social justice in Sub-Saharan Africa higher education institutions - Luvalo, L. M.; Linake, M.; Cishe, C.E (South African Journal of Higher Education, 2025)
This article explored the role of institutional culture in instilling social justice in the workplace, sometimes referred to as organisational justice. The concern is whether institutional culture plays any role in social justice at higher education institutions. In recent years, there has been an increasing interest in the role institutional culture can play in enhancing organisational justice, due to workplace injustices that persist at institutions of higher learning. In the past decade, research has focused on discrimination, gender issues and corruption in the workplace. However, there has been little focus on changing the organisational culture of an organisation where managers need employees to achieve their objectives, sometimes to the detriment of social justice. Employee job performance and satisfaction are considered key variables that can influence organisational performance, and this pressure may lead to work injustice and affect teaching and learning. In the process of describing the role institutional culture can play towards enhancing organisational justice, we used the views of academics, students and support staff and analysed institutional policies from several universities that are part of the space and spatiality project in Sub‒Saharan Africa by means of a qualitative enquiry. This article established that the culture of an institution plays a pivotal role in entrenching or affecting justice at institutions of higher education. The findings revealed that there is, generally, non‒non-compliance with institutional policies which affects teaching and learning, thereby contributing to workplace injustice which negatively affects various stakeholders in institutions of higher learning. The article recommends that an institutional‒wide policy monitoring and evaluation system be developed and implemented and that the culture of the institution be aligned with the policies in place.